Making Space for Stories: Communities, Narrative and Action - Leech, Angus (UnderCurrents: Journal of Critical Environmental Studies, 1999)
Human communities are inherently, intrinsically storied. The statement is at once obvious and in need of elaboration. That communities are composed of individuals and groups who tell each other stories almost goes without saying. Yet the role of these stories in influencing the interactions, identities and worldviews which exist within, and essentially define communities is a matter for some ponderance, and perhaps inestimable importance. [...]